CONCEPT AND ELEMENTS OF THE PRINCIPLE OF ACCESS TO JUSTICE - Siradeghyan, Tatevik (State and Law, 2023)
In the article, the author revealed the essence of the principle of access to justice, substantiated that it is not a component of the right to a fair trial, but the right to access to court. Considering the narrow and broad interpretation of the principle of access to justice, the author noted that only in the case of a narrow interpretation of this principle, it cannot be equated with the right of access to justice (the right of the court). In the article, the author presented the elements of the principle of access to justice, its various classifications in scientific research works. Summarizing the scientific and practical approaches to the principle of access to justice the author presented the concept of the principle of access to justice, separating from its elements legal, judicial, procedural, economic, organizational elements.
Keywords: the right to judicial protection; the right to a fair trial; justice; principle of access to justice; the right to access to a court; elements of the principle of access to justice